Heat propagation in computer designed and real metal foam structures. Issue 4 (14th November 2016) - August, Anastasia; Matz, Alexander M.; Nestler, Britta; Jost, Norbert
Abstract : Purpose: The purpose of this paper is to demonstrate a method for modeling of cellular structures by means of Voronoi tessellation and to conduct a validation by comparison with real metal foam structures. Design/methodology/approach: Heat propagation behavior of open-pore metal foams is studied for both experimental as well as computer-modeled structures showing excellent agreement. The 3D open-pore structure of the real foam is reconstructed from 2D light microscope images in-depth. Findings: An algorithm to create synthetic open-pore foam structures has been developed. Originality/value: The algorithm for modeling synthetic open-pore cellular structures allows the random distribution of the individual pores close to reality.